Evaluation of Bio-drying Process of Sewage Sludge using Mathematical Model of Heat and Mass Balance: Effects of Temperatures of Supplied Air and Exhaust Gas - Jae-Ram Park; Dong-Hoon Lee; Kyung-Hyun Kim (대한환경공학회지, 2020)
Objectives:The effects of temperatures of supplied air and exhaust gas on moisture removal in the bio-drying process of sewage sludge were assessed by simulating the process. We also suggested performance and efficiency indicators for moisture removal in this process and identified their effectivity. Methods:The bio-drying process of sewage sludge was simulated by mathematical modeling of heat and mass balance under different combinations of supplied-air temperatures and control ranges of exhaust gas temperatures. The simulation results were analyzed by using some indicators for assessing the performance and efficiency of moisture removal. Results and Discussion:While BVS (biodegradable volatile solid) degradation was inhibited at a higher supplied-air temperature and a lower control range of exhaust gas temperature, moisture reduction was enhanced at the supplied-air temperature nearer to ambient and the controlled exhaust gas temperature for 45 to 50℃. The drying performance could be improved by the utilization of both metabolic heat and convective heat from hot supplied-air for the source of heat necessary for moisture removal. We suggested the moisture removal rate as a performance indicator, and both the moisture removing capacity of supplied-air and the mass ratio of moisture removal to BVS degradation as an efficiency indicator. We identified that this mass ratio could be an alternative for thermal efficiency of drying. Conclusions:It is effective to control the air-flow rate to keep the exhaust gas temperature within 45~50℃ during bio-drying of sewage sludge in terms of drying performance and efficiency. It is expected that a specified range or minimum required value for the performance and efficiency indicators in the bio-drying process which suggested in this study needs to be established.